Evaluating the Impact of Information Literacy Workshops on Student Success - Shannon, Amanda; Skira, Aaron; Chen, Ying; Shreffler, Matt (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2025)
Objective – This study was designed to identify the impact of standalone information literacy tutorials on student success indicators. The study was conducted in two different phases to compare findings across different modalities and to identify whether online, asynchronous delivery of substantively similar content affected outcomes.Methods – Using institutional records from a mid-sized, Midwestern public university, and attendance and completion data from student participation in asynchronous library workshops, the authors used propensity score matching to construct a control group that mirrored library workshop participants based on like characteristics. Statistical analyses were then conducted comparing the GPA, semester completion, and retention rates between the two groups.Results – Students who completed at least one information literacy workshop had significantly higher semester GPAs (M = 3.25, SD = 0.85, SE = 0.06) than non-participants (M = 2.99, SD = 1.13, SE = 0.07); significantly higher semester completion rates (M = 0.93, SD = 0.18, SE = 0.01) than non-participants (M = 0.87, SD = 0.27, SE = 0.02); and substantially higher odds (OR = 3.5) of returning to the university the following semester than non-participants.Conclusion – The findings in this study provide evidence for librarians advocating for the benefit of information literacy instruction on student success, particularly for undergraduate student retention. Additionally, library instruction programs making decisions about where to focus resources will find the comparisons between outcomes for online and traditional methods of instruction informative.